Glutamate Metabolism in Brain Structures in Experimental Hemorrhagic Shock - V. N. Jakovlev; P. N. Savilov; Y. V. Bulgakova (Общая реаниматология)
Purpose. To study glutamate metabolism characteristics in phylogenetically different parts of the mammalian brain in experimentally induced hemorrhagic shock (HS) in cats.Material and methods. Experiments were performed on 76 cats. HS was induced by intermittent bloodletting from femoral artery at a rate of 10ml/kg•10 minutes, with the average volume of 24±0.8 ml/kg. The bloodletting was discontinued after arterial pressure (BP) drop to 60.0±1.5 mmHg. We studied ammonia, glutamate (Gt), and α-ketoglutarate (α-KG) levels and glutaminase (GS) and glutamate dehydrogenase (GDG) activity in specimens harvested from phylogenetically different parts of the brain (cortex, limbic system, diencephalon, and medulla oblongata).Results. In intact animals, the peak GDG activity was found in the medulla oblongata (phylogenetically the oldest part of the brain) and the peak GS activity was registered in the sensorimotor cortex (phylogenetically the youngest part of the brain); the glutaminase activity did not depend on the phylogenetic age of brain structures.In the case of HS, Gt metabolism changes began in the sensorimotor cortex manifested by decreased GS activity, which progresses by the 70th minute of the post%hemorrhagic period (PHP) accompanied by delayed increase in the GDG and glutaminase activity, as well as Gt accumulation. In the limbic system and diencephalon the Gt metabolism was changing (impaired glutamine synthesis, stimuled Gt synthesis with glutamine desamidization and α%KG amination) when developed by the 70th minute of the PHP. Similarly to sensorimotor cortex, changes were associated with Gt accumulation. During the agony, α%KG deficiency developed in all parts of the brain as a result of its increased contribution to Gt synthesis. At the same period of time, in the sensorimotor cortex, limbic system and diencephalon the Gt synthesis from glutamine was stimulated, however, the Gt contribution tothe formation of glutamine was decreased. The accumulation of ammonia regardless of the HS stage was detected only inthe sensorimotor cortex, limbic system and diencephalon; in the medulla oblongata ammonium increase was found only during the agony.Сonclusion. HS creates conditions for glutamate accumulation in nerve cells by impairing the metabolism of glutamate in the brain structures. The nature and scope of these disorders depend both on the intensity of glutamate metabolism in phylogenetically different brain structures in acute blood loss and HS.